Searching for Smart City definition: a comprehensive proposal (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
During the latest years, smart city projects have been more and more popular and widespread all over the world. The continuous increasing of cityâ€™s population and the complexity of city management drive local governments towards the strong use of technologies to support a higher quality of urban spaces and a better offering of public services. The fascination of smart cities, able to link high technology, green environment and well-being for citizens, interests all the municipalities, independently on their dimensions, geographical area or culture. However, the concept of smart city is far from to be unambiguous. Several experiences all over the world show that cities define themselves as smart, but the meaning attributed to this word is different each time. Smart city concept has been growing from empirical experience, therefore a systemic theoretical study about this phenomenon still lacks. In this paper, the author aims to propose a comprehensive and verified definition of smart city, based on both a deep literature investigation about smart city studies and a large survey of smart city projects in the international panorama. The goal of this work is not only to provide a clear framework about this interesting and current topic, but also to support local governments and public administrations in effective smart city implementation, able to create public value and well being for citizens and environmental sustainability in the urban space.Â